2008
DOI: 10.1038/bjp.2008.213
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of two‐pore‐domain (K2P) potassium leak channels by the tyrosine kinase inhibitor genistein

Abstract: Background and purpose: Two-pore-domain potassium (K 2P ) channels mediate potassium background (or 'leak') currents, controlling excitability by stabilizing membrane potential below firing threshold and expediting repolarization. Inhibition of K 2P currents permits membrane potential depolarization and excitation. As expected for key regulators of excitability, leak channels are under tight control from a plethora of stimuli. Recently, signalling via protein tyrosine kinases (TKs) has been implicated in ion c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 57 publications
1
34
0
Order By: Relevance
“…It is thus clear that one or more tyrosine kinases are responsible for swellingactivation of the K ϩ channels, which in EATC and EATCC are known to be TASK-2 channels. It has previously been shown that TASK-1 background current is inhibited by genestein and that an inhibitor of protein tyrosine phosphatase reduces this effect (12). In the present investigation it is demonstrated that inhibition of tyrosine phosphatases prevents the inhibitory effect of the tyrosine kinase inhibitor genistein on RVD.…”
Section: Tyrosine Kinases Are Involved In the Initiation Of Rvdsupporting
confidence: 56%
“…It is thus clear that one or more tyrosine kinases are responsible for swellingactivation of the K ϩ channels, which in EATC and EATCC are known to be TASK-2 channels. It has previously been shown that TASK-1 background current is inhibited by genestein and that an inhibitor of protein tyrosine phosphatase reduces this effect (12). In the present investigation it is demonstrated that inhibition of tyrosine phosphatases prevents the inhibitory effect of the tyrosine kinase inhibitor genistein on RVD.…”
Section: Tyrosine Kinases Are Involved In the Initiation Of Rvdsupporting
confidence: 56%
“…Twopore-domain potassium channel (K 2p ) genes such as KCNK17 (encoding K 2p 17.1, also known as TASK-4 and TALK-2) are known to be robustly expressed in myriad tissues, including cardiac and central nervous system, where they traditionally have been thought to regulate background cell excitability as leak channels (28,29). However, a wealth of transgenic animal studies support the notion that TASK family K 2p channels also strongly contribute to cardiac repolarization (30)(31)(32).…”
Section: Introductionmentioning
confidence: 99%
“…All experiments have been carried out in accordance with the United States National Institutes of Health Guide for the Care and Use of Laboratory Animals (NIH Publication no. 85-23, revised 1996) as reported earlier (Gierten et al, 2008;Staudacher et al, 2011b;Seyler et al, 2012). Briefly, oocytes were isolated from X. laevis ovarian lobes after surgical extirpation during tricaine anaesthesia (1 g L -1…”
Section: Oocyte Preparationmentioning
confidence: 99%